Lesotho: Non-development or under-development - Leys, Roger (My University, 1974)
This paper is intended as a re-examination of current thinking in the social sciences about Lesotho and, by extension, has I think some relevance to the analysis of the social formations and politics of those regions of Africa which Samir Amin has characterized as the economies of the labour reserve.
African Studies Seminar series. Paper presented October 1974
Keywords: Migrant labor. Lesotho; Lesotho. Economic conditions